Trehalose alleviates salt tolerance by improving photosynthetic performance and maintaining mineral ion homeostasis in tomato plants - Yang, Yan; Xie, Jianming; Li, Jing; Zhang, Jing; Zhang, Xiaodan; Yao, Yandong; Wang, Cheng; Niu, Tianhang; Bakpa, Emily Patience (Frontiers in Plant Science, 2022)
Trehalose (Tre), which was an osmoprotective or stabilizing molecule, played a protective role against different abiotic stresses in plants and showed remarkable perspectives in salt stress. In this study, the potential role of Tre in improving the resistance to salt stress in tomato plants was investigated. Tomato plants (Micro Tom) were treated with Hoagland nutrient solution (CK), 10mM Tre (T), 150mM sodium chloride (NaCl, S), and 10mM Tre+150mM NaCl (S+T) for 5d. Our results showed that foliar application of Tre alleviated the inhibition of tomato plant growth under salt stress. In addition, salt stress decreased the values of net photosynthetic rate (Pn, 85.99%), stomata conductance (gs, 57.3%), and transpiration rate (Tr, 47.97%), but increased that of intercellular carbon dioxide concentration (Ci, 26.25%). However, exogenous application of Tre significantly increased photosynthetic efficiency, increased the activity of Calvin cycle enzymes (ribulose diphosphate carboxylase/oxygenase (Rubisco), fructose-1,6-bisphosphate aldolase (FBA), fructose-1, 6-bisphosphatase (FBPase), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and transketolase (TK)), up-regulated the expression of genes encoding enzymes, induced stomatal opening, and alleviated salt-induced damage to the chloroplast membrane and structure. In the saline environment, photosynthetic electron transport was restricted, resulting the J-I-P phase to decrease. At the same time, the absorption, capture, and transport energies per excited cross-section and per active reaction center decreased, and the dissipation energy increased. Conversely, Tre reversed these values and enhanced the photosystem response to salt stress by protecting the photosynthetic electron transport system. In addition, foliage application with Tre significantly increased the potassium to sodium transport selectivity ratio (SK-Na) by 16.08%, and increased the levels of other ions to varying degrees. Principal component analysis (PCA) analysis showed that exogenous Tre could change the distribution of elements in different organs and affect the expressions of SlSOS1, SlNHX, SlHKT1.1, SlVHA, and SlHA-A at the transcriptional level under salt stress, thereby maintaining ion homeostasis. This study demonstrated that Tre was involved in the process of mitigating salt stress toxicity in tomato plants and provided specific insights into the effectiveness of Tre in mediating salt tolerance.